Chloride channels in stellate cells are essential for uniquely high secretion rates in neuropeptide-stimulated Drosophila diuresis. - Cabrero, P.; Terhzaz, S.; Romero, M.F.; Davies, S.A.; Blumenthal, E.M.; Dow, J.A. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Epithelia frequently segregate transport processes to specific cell types, presumably for improved efficiency and control. The molecular players underlying this functional specialization are of particular interest. In Drosophila, the renal (Malpighian) tubule displays the highest per-cell transport rates known and has two main secretory cell types, principal and stellate. Electrogenic cation transport is known to reside in the principal cells, whereas stellate cells control the anion conductance, but by an as-yet-undefined route. Here, we resolve this issue by showing that a plasma membrane chloride channel, encoded by ClC-a, is exclusively expressed in the stellate cell and is required for Drosophila kinin-mediated induction of diuresis and chloride shunt conductance, evidenced by chloride ion movement through the stellate cells, leading to depolarization of the transepithelial potential. By contrast, ClC-a knockdown had no impact on resting secretion levels. Knockdown of a second CLC gene showing highly abundant expression in adult Malpighian tubules, ClC-c, did not impact depolarization of transepithelial potential after kinin stimulation. Therefore, the diuretic action of kinin in Drosophila can be explained by an increase in ClC-a-mediated chloride conductance, over and above a resting fluid transport level that relies on other (ClC-a-independent) mechanisms or routes. This key segregation of cation and anion transport could explain the extraordinary fluid transport rates displayed by some epithelia.